Emerging treatments in Neurogastroenterology: Perspectives of guanylyl cyclase C agonists use in functional gastrointestinal disorders and inflammatory bowel diseases. Issue 8 (30th April 2015) - Jarmuż, A.; Zielińska, M.; Storr, M.; Fichna, J.
Abstract Background Functional gastrointestinal disorders (FGID) and inflammatory bowel diseases (IBD) are the most frequent pathologic conditions affecting the gastrointestinal (GI) tract and both significantly reduce patients' quality of life. Recent studies suggest that guanylyl cyclase C (GC‐C) expressed in the GI tract constitutes a novel pharmacological target in the treatment of FGID and IBD. Endogenous GC‐C agonists – guanylin peptides: guanylin and uroguanylin, by the regulation of water and electrolyte transport, are involved in the maintenance of homeostasis in the intestines and integrity of the intestinal mucosa. Linaclotide, a synthetic agonist of GC‐C was approved by Food and Drug Administration and European Medicines Agency as a therapeutic in constipation‐predominant irritable bowel syndrome (IBS‐C) and chronic idiopathic constipation (CIC). Lately, several preclinical and clinical trials focused on assessment of therapeutic properties of synthetic agonists of uroguanylin, plecanatide, and SP‐333. Plecanatide is currently tested as a potential therapeutic in diseases related to constipation and SP‐333 is a promising drug in ulcerative colitis treatment. Purpose Here, we discuss the most recent findings and future trends on the development of GC‐C agonists and their use in clinical trials.